Sustainability assessment and standardisation : steel buildings - Andrade, Joana B. (2012)
This paper aims at evaluating in what extent are the existing sustainability assessment methodologies capable of truly reward the benefits of steel-intensive buildings in comparison with other building construction solutions. This evaluation consists in describing the more common sustainability assessment methodologies from the steel construction point of view and in comparing existing assessments to steel buildings. The pros and cons of each will also be pointed out, in order to determine the best practices of each methodology.